Short-Term Distributional Effects of Structural Reforms Selected Simulations in a DGSE Framework - Mourougane, Annabelle (OECD Economics Department Working Papers, 2008)
This paper examines the short-term distributional effects of a number of tax and labour market reforms in the euro area, drawing on simulations using a micro-founded dynamic general equilibrium model. A heterogeneous household sector with two groups of consumers is considered. The first group maximises intertemporal utility over an infinite horizon in the presence of habit persistence. The second group is liquidity constrained and has no access to financial markets for intertemporal income transfers. It thus spends its disposable income entirely on current consumption. Although the examined reforms are estimated to boost aggregate consumption and output immediately after implementation, they have sizeable distributional effects. In particular, liquidity-constrained households may incur transitional losses after a cut in the benefit replacement ratio. Lowering employment and/or price adjustment costs could markedly reduce these short-term costs. A suitable compensation scheme could also reduce the uneven distribution of transitional losses, but at the expense of lower aggregate gains in the long run